Strategic Business Management for Startups in Vietnam’s Education and Healthcare Sectors: Exploring Cross-Sector Synergies for Sustainable Growth - Kim Hoa, Nguyen Thi (Digital Repository of Theses - SSBM Geneva, 2025)
This research explores strategic business management tailored for startups operating within Vietnam’s education and healthcare sectors, two critical pillars of the nation’s socio-economic development. Despite rapid sectoral growth, startups in these industries face persistent challenges including limited financial resources, underdeveloped management capabilities, regulatory complexities, and disparities in technological access—particularly between urban and rural areas. The primary objective of the study is to develop a personalized management system that enhances operational efficiency, adaptability, and competitiveness for startups in both sectors. The research employs a quantitative, descriptive-correlational methodology, gathering data from 221 participants comprising small and medium-sized enterprise (SME) owners and vocational students. Structured surveys and secondary data were used to identify key constraints and assess entrepreneurial readiness. Findings reveal that over 80% of SME owners struggle with accessing capital and report inadequate management skills as major barriers to growth. Only 18% of students feel prepared to pursue entrepreneurship, highlighting gaps in practical training and mentorship. However, the study also identifies strong enthusiasm for cross-sector collaboration and innovation, particularly in leveraging technology to bridge skills gaps and improve healthcare access through education-driven solutions. The study concludes that integrated strategic management, rooted in sector-specific needs and supported by technology, can significantly enhance startup sustainability. Recommended solutions include targeted capacity-building programs, simplified regulatory pathways, investment in digital infrastructure, and policy support for crosssector partnerships. By aligning education and healthcare through startup innovation, Vietnam can cultivate a robust ecosystem that drives inclusive growth and social wellbeing. This research contributes a practical framework for entrepreneurs, educators, and policymakers to co-create sustainable strategies that empower startups and amplify their impact across both sectors.